Oxidation response of additively manufactured eutectic Mo-Si-B alloys. Issue 1 (July 2020) - Becker, J; Fichtner, D; Schmigalla, S; Schultze, S; Heinze, C; Küsters, Y; Hasemann, G; Schmelzer, J; Krüger, M
Abstract: Previous studies showed the technical feasibility of additive manufacturing (AM) of Mo-Si-B alloys using the laser powder bed fusion (L-PBF) process. The competitiveness of the properties of AM alloys was demonstrated by a comparison to literature data from conventionally processed Mo-Si-B materials. In addition to the excellent mechanical properties at ambient and elevated temperatures, the oxidation resistance in a wide temperature range is another decisive aspect for the potential use of AM Mo-Si-B alloys. The present work shows investigations on the cyclic oxidation performance of a eutectic AM Mo-16.5Si-7.5B alloy. Depending on the temperature (800 °C, 1100 °C, 1300 °C), the oxidation mechanisms are different, which is due to different reactions at the surface of the alloys accompanied with mass changes of samples. These mass changes can be explained on the basis of microstructural investigations. However, compared to a directionally solidified (DS) alloy, the AM alloy shows improved oxidation resistance.